THE INFLUENCE OF BRAND IMAGE, PRICE AND PROMOTION ON PURCHASE DECISION (Case Study on Gea Geo Store) - Suhesti Ningsih; Sri Laksmi Pradanawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this the research is to know the influence of brand image, price, and promotion toward purchase decision of batik in Toko Gea Geo. This study uses a quantitative approach to the customer population in Gea Geo stores. Samples are taken using the calculation of Slovin formula. Data analysis using multiple linear regression model, F test, t test and R2 test. The results showed that simultaneously the variables of brand image, price and promotion had an effect on purchasing decisions. This is evidenced by the results of the F test has a significance value of 0.000